The Struggle to Write: Understanding and Overcoming Academic Writing Challenges in Higher Education - Ni Made Sindi Pratiwi (Indonesian Journal Publisher, 2026)
Academic writing is a fundamental competency in higher education; however, many university students, particularly those learning English as a Foreign Language (EFL), continue to experience persistent difficulties in mastering this skill. Despite the growing body of research on academic writing challenges, limited attention has been given to students’ perceptions of institutional and instructional support in Indonesian higher education contexts. This study aims to explore the main challenges faced by undergraduate students in academic writing and to examine how they perceive the support provided by lecturers, peers, and academic resources. Employing a qualitative descriptive research design, data were collected through a structured questionnaire administered to 30 undergraduate students from the English Language Education Department at UHN I Gusti Bagus Sugriwa Denpasar. The questionnaire addressed linguistic challenges, writing strategies, affective factors, and perceived academic support. The data were analyzed descriptively using SPSS to identify dominant patterns and tendencies. The findings indicate that students commonly struggle with organizing ideas, using appropriate academic vocabulary, managing time effectively, and applying grammar and referencing conventions accurately. While lecturer guidance and peer feedback were generally perceived as supportive, access to institutional writing resources such as writing centers and workshops was considered limited or unclear by many students. These results suggest that academic writing difficulties are multidimensional, involving linguistic, cognitive, affective, and institutional factors. The study highlights the importance of structured writing instruction, continuous formative feedback, and enhanced institutional support systems to improve students’ academic writing competence. The findings contribute to the ongoing discussion on EFL academic writing pedagogy and provide practical implications for lecturers and higher education institutions.